Material and structural tensile properties of the human medial patello-femoral ligament. (February 2016) - Criscenti, G.; De Maria, C.; Sebastiani, E.; Tei, M.; Placella, G.; Speziali, A.; Vozzi, G.; Cerulli, G.
Abstract: The medial patellofemoral ligament (MPFL) is considered the most important passive patellar stabilizer and acts 50–60% of the force of the medial soft-tissue which restrains the lateralization of the patella between 0° and 30°. In this work, 24 human knees have been tested to evaluate the material properties of MPFL and to determine the structural behavior of femur-MPFL-Patella complex (FMPC). Particular attention was given to maintain the anatomical orientation between the patella and MPFL and to the evaluation of the elongation during the mechanical tests. The ultimate stress of the isolated ligament was 16±11 MPa, the ultimate strain was 24.3±6.8%, the Young׳s Modulus was 116±95 MPa and the strain energy density was 2.97±1.69 MPa. The ultimate load of the whole structure, FMPC, was 145±68 N, the ultimate elongation was 9.5±2.9 mm, the linear stiffness was 42.5±10.2 N/mm and the absorbed energy was 818.8±440.7 N mm. The evaluation of material and structural properties of MPFL is fundamental to understand its contribution as stabilizer and for the selection of repair and reconstruction methods. Graphical abstract: Highlights: The medial patellofemoral ligament (MPFL) is considered the most important passive patellar stabilizer. 24 human knees have been tested to evaluate the material properties of MPFL and to determine the structural behavior of femur-MPFL-patella complex (FMPC). The ultimate stress of the MPFL was 16±11 MPa while the ultimate load of the FMPC was 145±68 N. Provided results can be useful for the selection of most performing repair methods.